2018
DOI: 10.1039/c8ra01555d
|View full text |Cite
|
Sign up to set email alerts
|

Organ preservation with targeted rapamycin nanoparticles: a pre-treatment strategy preventing chronic rejection in vivo

Abstract: (a) Rapamycin nanotherapeutic pre-treatment improves tracheal allograft outcome after transplantation. (b) Nanotherapy reduces aortic allograft vasculopathy. (c) Dose dependency of the nanotherapy in aortic interposition allografts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 31 publications
(64 reference statements)
0
22
0
Order By: Relevance
“…For instance, the modification of antibodies on PLGA NPs successfully moderated the chronic rejection of transplanted heart by targeting IL-6 secreted by allograft-derived dendritic cells (ADDCs) (Solhjou et al, 2017 ). Furthermore, the endothelial cell inflammation and pro-inflammatory cytokines secretion following tracheal or aortic allografts could be greatly attenuated by the pre-treatment of rapamycin (Nadig et al, 2015 ; Zhu et al, 2018 ).…”
Section: Alternative Strategies For Iri Therapy and Organ Transplantamentioning
confidence: 99%
“…For instance, the modification of antibodies on PLGA NPs successfully moderated the chronic rejection of transplanted heart by targeting IL-6 secreted by allograft-derived dendritic cells (ADDCs) (Solhjou et al, 2017 ). Furthermore, the endothelial cell inflammation and pro-inflammatory cytokines secretion following tracheal or aortic allografts could be greatly attenuated by the pre-treatment of rapamycin (Nadig et al, 2015 ; Zhu et al, 2018 ).…”
Section: Alternative Strategies For Iri Therapy and Organ Transplantamentioning
confidence: 99%
“…In vitro tests by MTT showed no cytotoxicity of empty micelles, loaded with rapamycin (targeted or untargeted), or free rapamycin up to concentrations of 3 μg/ml after 6 h. Additionally, in vitro targeting demonstrated, and inflammatory markers (IL-6 and IL-8) were decreased; these results were confirmed in a C57 mouse model [77]. This same group recently provided evidence that this targeted formulation could be used as an additive and pretreatment regimen to prevent chronic rejection in vivo [78].…”
Section: Rapamycinmentioning
confidence: 83%
“…This study further demonstrated that during cold preservation for 4-6 h, receptor-mediated endocytosis of rapamycin-loaded micelles can potentially reduce the secretion of inflammatory cytokines. 49 Collectively, these studies demonstrate that during standard allograft procurement procedures, endothelial cells of the allografts can be readily targeted by NPs to reduce post-transplant allograft injury and potentially promote long-term allograft survival.…”
Section: Nanotechnology For Promoting Long-term Transplant Survivalmentioning
confidence: 88%
“…47 Employing normothermic machine perfusion of human kidneys, Tietjen et al 48 demonstrated that endothelial cells could be targeted by an anti-CD31 antibody conjugated to poly(lactic acid)-poly (ethylene) glycol NPs. In another recent study, Zhu et al 49 demonstrated that incubating mouse tracheal and aortic allografts with rapamycin-loaded polyethylene glycol micelles (10 nM in size) in standard hypothermic University of Wisconsin (UW) solution significantly prevents the chronic rejection of these allografts post-transplantation. This study further demonstrated that during cold preservation for 4-6 h, receptor-mediated endocytosis of rapamycin-loaded micelles can potentially reduce the secretion of inflammatory cytokines.…”
Section: Nanotechnology For Promoting Long-term Transplant Survivalmentioning
confidence: 99%